COMPREHENDING THE ESSENSE OF THE PARSAHUTAON COMMUNITY IN NURTURING INTERFAITH SOLIDARITY IN TARUTUNG CITY, NORTH SUMATRA - Gideon Hasiholan Sitorus (Jurnal Sosiologi Reflektif, 2023)
Interreligious relations become an integral part of the discourse of social parity. The creation of harmony between individuals and groups is very important to review, given that human existence is filled with dynamic aspects, such as culture, situation, and context. This study aims to describe and examine the essence of the existence of Parsahutaon social associations in building social solidarity between religious people in Tarutung City, North Sumatra. A descriptive qualitative methodology was utilized in this research, with literature review serving as the primary data collection technique. The results showed that a prosocial essence was present in the Parsahutaon community. First, it becomes the foundation for realizing compliance in the midst of plurality. Second, the means of implementation in the construction of social solidarity amidst the diversity of faith traditions in the city of Tarutung.Relasi antar umat beragama menjadi bagian yang tidak terpisahkan dari wacana paritas sosial. Terciptanya harmoni antar individu dengan kelompok sangat penting untuk dikaji ulang, mengingat bahwa eksistensi manusia dipenuhi dengan aspek dinamis, seperti: budaya, situasi dan konteks. Penelitian ini bertujuan mendeskripsikan dan menelisik esensi dari keberadaan asosiasi sosial Parsahutaon dalam membangun solidaritas sosial antar umat beragama di Kota Tarutung, Sumatera Utara. Penelitian dilakukan dengan menggunakan pendekatan kualitatif deskriptif melalui studi pustaka sebagai teknik pengumpulan data. Hasil penelitian menunjukkan bahwa, komunitas Parsahutaon memuat esensi yang prososial.  Pertama, menjadi basis terwujudnya konformitas di tengah pluralitas. Kedua, sarana sarana aplikatif dalam membangun solidaritas sosial di tengah keberagaman tradisi iman di Kota Tarutung.